The short-term results of an MI-adapted and culturally tailored intervention on self-reported oral health behaviors of indigenous caregivers and their children - Kirby, Christine; Baldwin, Julie; Elwell, Kristan (Frontiers in Oral Health, 2025)
IntroductionAmerican Indian (AI) children have the highest incidence of dental caries of any ethnic group with 4 times the cases of untreated dental caries compared to white children. Great Beginnings for Healthy Native Smiles (NIDCR U01DE028508), a community focused oral health intervention, included culturally tailored oral health education materials utilized alongside adapted motivational interviewing (MI) techniques to promote oral health care and education at home.MethodsThe intervention was conducted by local community members from two partnered Indigenous communities. Using formative assessment data from semi-structured caregiver and provider interviews, session transcript data, and debriefing interview data from participants post-intervention, the objective of this study was to determine the impact of culturally tailored oral health education focused on behavior change in each community.ResultsResults suggest that discussion with community health representatives using adapted MI and culturally tailored materials can result in self-reported behavioral change.DiscussionThe findings highlight the importance of involving trusted community health workers in delivering culturally tailored oral health messages for mothers and their children to reduce ECC.